I–V Characteristics and Electrical Reliability of Metal–SixNy–Metal Capacitors as a Function of Nitrogen Bonding Composition - Tae-Min Choi; Eun-Su Jung; Jin-Uk Yoo; Hwa-Rim Lee; Songhun Yoon; Sung-Gyu Pyo (Micromachines)
In this study, we analyzed the electrical characteristics of metal–insulator–metal (MIM) capacitors fabricated with reference to insulator (SixNy) thickness and deposition condition. SixNy thicknesses of 650 Å, 500 Å, and 400 Å were used with four different conditions designated as MIM (N content 1.49), NEWMIM (N content 28.1), DAMANIT (N content 1.43), and NIT (N content 0.30), deposited by controlling gas flow and RF power as a function of N content. Capacitor characteristics were evaluated mainly in terms of the relationship between leakage current and breakdown voltage (BV). Current–voltage (I–V) characterizations revealed that a higher N–H/Si–H ratio effectively suppressed trap-assisted leakage conduction and enhanced dielectric robustness under high-field stress. Among the tested conditions, the NEWMIM process demonstrated the most favorable electrical performance with highest N contents. The MIM and NEWMIM conditions proved most effective among the evaluated processes, achieving sufficient BV values (>20 V) for reliable MIM capacitor operation and proposing a process optimization framework for integrating medium-density SixNy–based MIM capacitors (2 fF/µm2) with sufficiently high BV values in the future.